Guest‐Induced Breathing Effect in a Flexible Molecular Crystal. (2nd February 2016) - Sheng, Yujie; Chen, Qibin; Yao, Junyao; Lu, Yunxiang; Liu, Honglai; Dai, Sheng
Abstract: By introducing a flexible component into a molecular building block, we present an unprecedented alkyl‐decorated flexible crystalline material with a breathing behavior. Its selective adsorption is derived from the breathing effect induced by a guest triggered alkyl transformation. This feature allows the crystal to take up 2.5 mmol g −1 of chloroform with high adsorption selectivity (CHCl3 /EA >2000 for example), implying a potential application in sorption separation and chemical sensors.